2019
DOI: 10.1101/736389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LUZP1 and the tumour suppressor EPLIN are negative regulators of primary cilia formation

Abstract: Running title: LUZP1 and EPLIN regulate ciliogenesis SUMMARY Gonçalves et al. show that LUZP1 and its interactor EPLIN are negative regulators of ciliogenesis. LUZP1 is a novel actin-stabilizing protein localizing at the centrosome and basal body where it may regulate actin-associated processes. 2 ABSTRACT Cilia/flagella are microtubule-based cellular projections with important sensory and motility functions. Their absence or malfunction is associated with a growing number of human diseases collectively referr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Two independent proximity labeling studies identified LUZP1 as a proximal interactor of centriole ( Gupta et al, 2015 ) and centriolar satellite-related proteins ( Gheiratmand et al, 2019 ). Moreover, LUZP1 has been recently reported as a centrosomal protein involved in cilia regulation ( Gonçalves et al, 2019 ). These localizations are also consistent with fluorescent LUZP1 fusion proteins (this work; [ Gupta et al, 2015 ; Gonçalves et al, 2019 ] #117).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two independent proximity labeling studies identified LUZP1 as a proximal interactor of centriole ( Gupta et al, 2015 ) and centriolar satellite-related proteins ( Gheiratmand et al, 2019 ). Moreover, LUZP1 has been recently reported as a centrosomal protein involved in cilia regulation ( Gonçalves et al, 2019 ). These localizations are also consistent with fluorescent LUZP1 fusion proteins (this work; [ Gupta et al, 2015 ; Gonçalves et al, 2019 ] #117).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LUZP1 has been recently reported as a centrosomal protein involved in cilia regulation ( Gonçalves et al, 2019 ). These localizations are also consistent with fluorescent LUZP1 fusion proteins (this work; [ Gupta et al, 2015 ; Gonçalves et al, 2019 ] #117). Discrepancies with the previously reported LUZP1 localization and distribution might be due to technical differences, such as epitope specificity for the antisera used in the immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…To date, proximity mapping has been used to mechanistically dissect these processes using both targeted and systematic approaches. As for the targeted approaches, proximity interaction maps were generated for known regulators of cilium assembly as well as proteins mutated in ciliopathies including CEP72, CCDC66, CEP104, MIB1, ARL13B, CDC14A, LUZP1 and CEP120 [122,129,130,132,[134][135][136]151]. As with centriole duplication, these maps identified new functional modules required for specific steps of cilium assembly and revealed mechanisms that underlie ciliopathies.…”
Section: Primary Cilium Biogenesis and Proteomementioning
confidence: 99%
“…Another new discovery unveiled from proximity mapping is the regulatory relationship between the actin cytoskeleton and ciliogenesis. The actin-stabilizing protein LUZP1 and its interactor SALL1 had proximity interactions with centrosome and cilium proteins [134,135,139]. Their further characterization identified them as regulators of cilium assembly and Hedgehog signaling, and suggested mechanisms that underlie the Townes-Brocks syndrome.…”
Section: Primary Cilium Biogenesis and Proteomementioning
confidence: 99%
“…LUZP1 encodes a ciliary basal body protein that has recently been shown to play important roles in regulating ciliogenesis. 45,46 While there is no Mendelian disease yet known to result from disruption of the LUZP1 gene, recent work has shown reduced LUZP1 expression in fibroblasts derived from Townes-Brockes syndrome (characterized by renal disease, among other findings) patients, 47 suggesting that LUZP1 may play a role in the pathogenesis of this disorder.…”
Section: Luzp1mentioning
confidence: 99%